Eleven tips for operational researchers working with health programmes: our experience based on implementing differentiated tuberculosis care in south India. Issue 1 (31st December 2023) - Shewade, Hemant Deepak; Frederick, Asha; Kalyanasundaram, Madhanraj; Chadwick, Joshua; Kiruthika, G.; Rajasekar, T. Daniel; Gayathri, K.; Vijayaprabha, R.; Sabarinathan, R.; Shivakumar, Shri Vijay Bala Yogendra; Jeyashree, Kathiresan; Bhavani, P. K.; et al.
ABSTRACT: Due to the workload and lack of a critical mass of trained operational researchers within their ranks, health systems and programmes may not be able to dedicate sufficient time to conducting operational research (OR). Hence, they may need the technical support of operational researchers from research/academic organisations. Additionally, there is a knowledge gap regarding implementing differentiated tuberculosis (TB) care in programme settings. In this 'how we did it' paper, we share our experience of implementing a differentiated TB care model along with an inbuilt OR component in Tamil Nadu, a southern state in India. This was a health system initiative through a collaboration of the State TB cell with the Indian Council of Medical Research institutes and the World Health Organisation country office in India. The learnings are in the form of eleven tips: four broad principles (OR on priority areas and make it a health system initiative, implement simple and holistic ideas, embed OR within routine programme settings, aim for long-term engagement), four related to strategic planning (big team of investigators, joint leadership, decentralised decision-making, working in advance) and three about implementation planning (conducting pilots, smart use of e-tools and operational research publications at frequent intervals). These may act as a guide for other Indian states, high TB burden countries that want to implement differentiated care, and for operational researchers in providing technical assistance for strengthening implementation and conducting OR in health systems and programmes (TB or other health programmes). Following these tips may increase the chances of i) an enriching engagement, ii) policy/practice change, and iii) sustainable implementation.